A de-novo STXBP1 gene mutation in a patient showing the Rett syndrome phenotype. Issue 5 (25th March 2015) - Romaniello, Romina; Saettini, Francesco; Panzeri, Elena; Arrigoni, Filippo; Bassi, Maria T.; Borgatti, Renato
Abstract : This study reports on a 9-year-old girl who developed West syndrome and showed clinical features fulfilling the main revised diagnostic criteria for typical Rett syndrome (hand washing, severe cognitive impairment with absence of language, ataxic gait, progressive scoliosis and autistic features). Mutation analyses for methyl-CpG-binding protein 2 ( MECP2 ), cyclin-dependent kinase-like 5 ( CDKL5/STK9 ), ARX and Forkhead box G1 ( FOXG1 ) genes were carried out, with negative results. A known de-novo c.1217G>A missense mutation in exon 14 leading to the substitution of a conserved residue, p.R406H in domain3b of the syntaxin-binding protein 1 ( STXBP1 ) gene, was detected. The STXBP1 gene encodes the syntaxin-binding protein 1, a neuron-specific protein involved in synaptic vesicle release at both glutaminergic and GABAergic synapses. This function is also affected by MECP2 gene mutations, which are known to lead to a decrease in glutamate and GABA receptors' density. It is possible to speculate that the impairment in synaptic plasticity represents the pathogenic link between MECP2 and STXBP1 gene mutations. On reviewing the clinical features of the reported patients with the same mutation in the STXBP1 gene, it has been observed that poor eye contact, tremour, dyskinesia, head/hand stereotypies and both cognitive and motor progressive deterioration are common symptoms, although never considered as indicative of a Rett syndrome phenotype. In conclusion, the case described here suggests a relationship between the Rett syndrome and the STXBP1 gene not described so far, making the search for STXBP1 gene mutations advisable in patients with Rett syndrome and early onset of epilepsy.